Effect of Corporate Governance Structures, Political Connections, and Transfer Pricing on Tax Aggressiveness - Kenny Ardillah; Yola Vanesa (Faculty of Economics, Universitas Sriwijaya, 2022)
This study examines and analyzes the effect of corporate governance structures, political connections, and transfer pricing on tax aggressiveness (CETR and BTD). The theory used in this study is agency theory. The sample of this study is manufacturing companies listed on the Indonesia Stock Exchange for 2014-2019. The sampling method used in this study was purposive sampling and used multiple linear regression as the data analysis method. The results of the study using the cash effective tax rates (CETR) proxy shows that the independent board has a positive effect on tax aggressiveness, the audit committee has a negative effect on tax aggressiveness, political connections do not affect tax aggressiveness, and transfer pricing does not affect tax aggressiveness. The result of the study with a book-tax difference (BTD) proxy shows that independent commissioners do not influence tax aggressiveness, audit committees positively affect tax aggressiveness, political connections do not affect tax aggressiveness, and transfer pricing does not affect tax aggressiveness. The implication of this study reveals that the companies should follow tax regulations made by the government to do tax planning under applicable laws.